(untitled) (International Journal of Physiotherapy, 2021)
Background: The effect of harvesting peroneus longus tendon graft (PLTG) for anterior Cruciate ligament reconstruction (ACLR) on donor ankle stability and function and its effect on overall body balance is not yet investigated. PLT is thought to play some role in the proprioceptive regulation of the ankle joint. ACL too has a vital role in the postural control of the knee joint. This study evaluates and compares the affected and sound limb balance and function in subjects following ACLR with autologous PLTG. Methods: A total of 44 eligible participants were assessed for balance using the HUMAC balance system and function with the Foot Ankle Ability Measure (FAAM) scale at 6week, 3month, and 6month after ACLR with PLTG. Outcome measures were stability score, path length, average velocity, time on target, and FAAM score. Results: There was statistically significant improvement in all the parameters of bilateral or unilateral standing balance at 6month post-op [Bilateral: stability score: p=0.001; path length: p=0.000; average velocity: p=0.000; time on target: p=0.006]; [unilateral-affected/sound: path length: p=0.000, p=0.003; average velocity: p=0.000, p=0.009). The difference between affected and sound limb balance was insignificant. Median of FAAM score at 6week, 3month, & 6month were 97.368, 98.809 and 100 respectively. Conclusion: Balance of the whole body or any single leg stability is impaired after ACLR with PLTG, but it may improve to an optimal level with due time and recover fully by six months. Donor ankle function also restores to 100% at 6month.